Three‐Dimensional Interlocking Interface: Mechanical Nanofastener for High Interfacial Robustness of Polymer Electrolyte Membrane Fuel Cells. Issue 2 (10th November 2016) - Yuk, Seongmin; Choo, Min‐Ju; Lee, Dongyoung; Guim, Hwanuk; Kim, Tae‐Ho; Lee, Dai Gil; Choi, Sungyu; Lee, Dong‐Hyun; Doo, Gisu; Hong, Young Taik; Kim, Hee‐Tak
Abstract : A scalable nanofastener featuring a 3D interlocked interfacial structure between the hydrocarbon membrane and perfluorinated sulfonic acid based catalyst layer is presented to overcome the interfacial issue of hydrocarbon membrane based polymer electrolyte membrane fuel cells. The nanofastener‐introduced membrane electrode assembly (MEA) withstands more than 3000 humidity cycles, which is 20 times higher durability than that of MEA without nanofastener.